Przemoc wobec dziecka w rodzinie - Błeszyński, Jacek J.; Rodkiewicz-Rożek, Anita (Oficyna Wydawnicza ATUT - Wrocławskie Wydawnictwo Oświatowe, 2012)
The article presents the problem of child abuse in the family. Shows the causes of violence in the family, but also treats children’s rights under the Convention on the Rights of the child, such as the right to an identity, right to expression, the right to live without violence, the right to social assistance, right to education. This article presents the family as the basic environment in which the child is born and brought up, because it has strong influence on the shaping of his personality. Refers to the fact that the home should be a place where the child feels safe. Pointed out that often but this is different, because victims of domestic violence are mostly women and children, as being weak and defenseless against their persecutors. The definition of domestic violence was quoted. Pointed to factors that protection children from violence, as well as the factors which contribute to harming. Defined physical violence against the child, and refers to the normative acts in this area, established as the sexual exploitation of children, studies showing the extent of the problem, and also refers to the legislation, to protect the child from sexual abuse.
Keywords: przemoc; dziecko; rodzina